2019
DOI: 10.1016/j.ygyno.2019.08.014
|View full text |Cite
|
Sign up to set email alerts
|

MTDH/AEG-1 downregulation using pristimerin-loaded nanoparticles inhibits Fanconi anemia proteins and increases sensitivity to platinum-based chemotherapy

Abstract: h i g h l i g h t sEndometrial cancer patients with high copy number of MTDH show poor outcome.Inhibition MTDH increases DNA damage induced g-H2Ax foci formation and sensitivity to cisplatin.MTDH binds with mRNAs encoding for FANCD2 and FANCI. Pristimerin-loaded nanoparticles inhibit MTDH, FANCD2 and FANCI to increase sensitivity to cisplatin. a b s t r a c tObjective: Platinum compounds have been widely used as a primary treatment for many types of cancer. However, resistance is the major cause of therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…However, the RNA interactome was not characterized, and it was documented that the protein levels of two AEG-1-interacting mRNAs, PDCD11 and KDM6A, were increased in AEG-1 knockdown cells, and the consequence of this observation was not studied [ 134 ]. In a follow-up study, the authors showed that, using residues 145-216, AEG-1 bound to mRNAs of FANCD2 and FANCI, two components of the Fanconi anemia complementation group that play an important role in interstrand crosslink damage induced by platinum compounds, increased their protein levels [ 184 ]. A positive correlation among the levels of AEG-1, FANCD2 and FANCI were observed in breast and endometrial cancers.…”
Section: Astrocyte-elevated Gene-1 (Aeg-1): An Oncogene Implicated In Diverse Cancersmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the RNA interactome was not characterized, and it was documented that the protein levels of two AEG-1-interacting mRNAs, PDCD11 and KDM6A, were increased in AEG-1 knockdown cells, and the consequence of this observation was not studied [ 134 ]. In a follow-up study, the authors showed that, using residues 145-216, AEG-1 bound to mRNAs of FANCD2 and FANCI, two components of the Fanconi anemia complementation group that play an important role in interstrand crosslink damage induced by platinum compounds, increased their protein levels [ 184 ]. A positive correlation among the levels of AEG-1, FANCD2 and FANCI were observed in breast and endometrial cancers.…”
Section: Astrocyte-elevated Gene-1 (Aeg-1): An Oncogene Implicated In Diverse Cancersmentioning
confidence: 99%
“…A positive correlation among the levels of AEG-1, FANCD2 and FANCI were observed in breast and endometrial cancers. Knocking out AEG-1 increased the cisplatin sensitivity in endometrial cancer cells, but a direct role of FANCD2 and FANCI in mediating this effect was not tested by overexpression/knockdown studies [ 184 ].…”
Section: Astrocyte-elevated Gene-1 (Aeg-1): An Oncogene Implicated In Diverse Cancersmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on previous findings, RBP-, miRNA-, and lncRNA-mediated post-transcriptional regulatory processes also play important roles in regulating the sensitivity to chemotherapeutic agents. 17 , 18 , 19 For the ovarian cancer cells displayed in Figure 8 A, the 50% inhibitory concentration (IC 50 ) of cisplatin was measured. Compared with the IC 50 value of the NC group, the IC 50 values of CELF2-overexpressing CAOV-3 and SK-OV-3 cells were decreased, and the values of CELF2-knockdown A2780 and OVCAR-8 cells increased after treatment with different concentrations of cisplatin, suggesting that the upregulation of CELF2 may be a promising strategy to increase the sensitivity of ovarian cancer cells to cisplatin.…”
Section: Resultsmentioning
confidence: 99%